Jewish Medal of Honor Recipients : American Heroes - Lanning, Michael Lee (Book collections on Project MUSE., 2022)
"Jewish Americans have fought in every war and conflict to protect the liberties and freedoms of their country, despite anti-Semitism and prejudices they encountered. Across differences of time, place, and individual background, the heroic service members profiled in this work share a common factor beyond their Jewish heritage: their deeds moved a grateful nation to bestow upon them its greatest military honor. In Jewish Medal of Honor Recipients: American Heroes, veteran author Michael Lee Lanning presents the stories and official citations of Jewish service members who joined the US Armed Forces' most exclusive group through their bravery and self-sacrifice in combat. From the total to date of 3,526 service members who have received the Medal of Honor, Lanning has identified 17 recipients who are confirmed to be Jewish, 11 more who are thought to be Jewish but whose ethnicity has not been fully verified, and another five who were initially recognized as Jewish at the time of award but who have since been determined not to be. Each of these 33 men receives individual attention as Lanning delves into their backgrounds with brief biographies to show the different paths that brought them to their place on the list of honor. He includes the full award citation for each as well. Jewish Medal of Honor Recipients: American Heroes is the result of thorough review of archival sources, interviews with surviving family members, newspaper accounts, and military service records, providing testimony to extraordinary deeds, service, and sacrifice"--